Recent Developments in Nuclear Magnetic Resonance Imaging and Flow Measurements - Crooks, Lawrence E. (IEEE transactions on nuclear science, 1984)
All instruments used to produce nuclear magnetic resonance (NMR) images have a number of common features. A strong, uniform, and stable magnetic field has to be imposed through the subject. This field has to be varied in space and time to define the location of pixels in the image. A radiofrequency magnetic field is applied to excite the nuclei. The radiofrequency signal from the nuclei is detected and its strength determines the intensities of the pixels in the image. The imaging process, data acquisition, and display are all controlled by computers. Within this general structure many options exist for collecting the data necessary for image reconstruction.